Performance of a guideway seismic isolator with magnetic springs for precision machinery. - Yao, George C. (Earthquake engineering & structural dynamics.)
This paper proposes the use of the nonlinear restoring force in an isolation system to improve the performance of a seismic isolator. Nonlinear magnetic springs applied to guideway sliding isolators (GSI) that protect precision machinery against seismic motion were studied. The magnetic springs use a non-contact magnetic repulsion force to achieve a nonlinear property. A numerical simulation model of the GSI system using step-by-step integration in the time domain was developed. A full-scale shaking table test was performed to verify the accuracy of the numerical model. Simulation and experimental results show that the GSI system with magnetic springs has good performance when subjected to floor vibrations during earthquakes. A parametric analysis of the magnetic springs in the GSI system under seismic motion was theoretically investigated. It was found that sufficient magnetic forces can diminish the system relative displacements.